Selfie: A Rising Culture. Assessment of Selfitis and Its Relation with Self-Esteem among Medical and Nursing Students: A Cross-Sectional Study - Raghavendra Nagaraju; Lokesh K Chikkegowda (Medsci Publications, 2019)
Introduction: Selfitis (the obsessive taking of selfies) is classified as a mental disorder by the American Psychiatric Association and is said to be associated with low self-esteem levels. Assessment of selfitis using Selfitis Behaviour Scale is unique among Indian stud- ies. This study conducted to estimate the burden of selfitis and its relation with self-esteem among medical and nursing students. Methodology: A cross-sectional study was conducted among med- ical and nursing students. Information regarding selfie clicking and posting on social media was collected by a structured questionnaire. Selfitis was assessed by using Selfitis Behaviour Scale (SBS) and self- esteem was assessed by using Rosenberg Self Esteem Scale. Results: This study included 347 students (123 males and 224 fe- males). Majority i.e., 225 (64.8%) of the study participants took selfies on any specific occasion, 300 (86.5%) of them took selfies with friends/ family members and 109 (31.4%) of them posted selfies on social medias. According to the scores of SBS, 169 (48.7%) of them had borderline selfitis, 63 (18.2%) of them had acute selfitis and 13 (3.7%) of them had chronic selfitis. Low self-esteem was seen in 105 (30.3%) of the study participants. Conclusion: Selfitis was seen in nearly quarter of the study partici- pants and there was no association between selfitis and self-esteem in this study.